Specialist doctor's professionalism on doctor's performance with job satisfaction as an intervening variable - Wilantara, Shabrina Salsabila Putri; Wanasida, Albert Surya (Institute of Computer Science (IOCS), 2024)
This research was conducted to determine the influence of professionalism of specialist doctors on doctor performance with job satisfaction as an intervening variable. This research was conducted at XYZ Palembang Hospital involving 36 specialist doctors. Data collection was carried out by distributing a questionnaire containing 59 questions with a Likert Scale of 1–5 based on the purposive sampling method. Data were analyzed using the PLS-based SEM method. The results of this research state that time management has a positive and significant effect on job satisfaction, job satisfaction has a negative effect and can mediate the effect of time management and training on the performance of specialist doctors. Motivation and training have a positive and insignificant effect on job satisfaction. Time management and motivation have a positive and insignificant effect on the performance of specialist doctors. Training and job satisfaction have a negative and insignificant effect on the performance of specialist doctors. Job satisfaction has a negative effect and is unable to mediate the influence of motivation on the performance of specialist doctors at xyz hospital in Palembang City